Current approaches to diagnosis, treatment, support and rehabilitation of patients after a stroke - Aymedov, K. V.; Grigoryev, E. O.; Luzhetska, N. A. (Journal of Education, Health and Sport, 2016)
The authors focus their attention on the relevance and prevalence of cardiovascular diseases among whom a significant percentage is occupied by strokes. For every 100 million people there are about 500 thousand strokes and cerebral vascular crises per year. The urgency of this problem causes a high percentage of disability patients (15-30%). Primary diagnosis and early intervention play an important role in the further rehabilitation of stroke patients. The authors note the urgent need to revise the methods of early diagnosis and the use of modern technologies in diagnosis. Synthesis and analysis of scientific and theoretical achievements and the results of experimental studies was aimed at examining modern research methods with the aim of choosing an adequate diagnostic method and isolating the main neurosurgical markers in individuals who had suffered a stroke.